Archaeological excavations at Gradina sv. Ivana on the island of Korčula (In situ, 2024)
The paper presents the results of archaeological excavations at the hill of Gradina with the church of St. John, located on the far western part of the island Korčula, that greatly improved the understanding of the dynamics of the use of this location and enabled its placing within the already known framework of prehistoric, ancient, medieval and modern settlement not only of the island of Korčula, but also of the entire surrounding archipelago.
Keywords: Hillfort; Korčula; Bronze Age; Late Antiquity; Medieval period